2016
DOI: 10.1039/c6cp05653a
|View full text |Cite
|
Sign up to set email alerts
|

Liquid silver tris(perfluoroethyl)trifluorophosphate salts as new media for propene/propane separation

Abstract: propene at 30 1C. This makes them promising separation materials for both liquid membranes and absorber fluids due to their high silver content and significant propene capacity. Single (iGSC) and mixed (NMR) gas solubilities as well as diffusion coefficients (PFG-NMR) of propene and propane were determined to predict the theoretical selectivity of solubility, membrane selectivity, capacity and transport properties of the silver salts according to the solution diffusion model. A strong influence of the number a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…1.924(2), 1.933(2) for 1a [43a] and 1.932(8), 1.911(8) for 1b [42c] ). The structure reveals the presence of the mer-isomer of the FAP anion in agreement with the 19 FNMR spectrumi ns olution, which shows only the signals of this isomer.T he solid-state structures of the metal complexespresented previously by Mochida and Kimata [39] and Wasserscheid et al [38] as well as the fluorophosphonium salt reported by Hoge et al [36] also contain the mer-isomero ft he FAP anion.…”
Section: Nickel Complexesmentioning
confidence: 66%
See 1 more Smart Citation
“…1.924(2), 1.933(2) for 1a [43a] and 1.932(8), 1.911(8) for 1b [42c] ). The structure reveals the presence of the mer-isomer of the FAP anion in agreement with the 19 FNMR spectrumi ns olution, which shows only the signals of this isomer.T he solid-state structures of the metal complexespresented previously by Mochida and Kimata [39] and Wasserscheid et al [38] as well as the fluorophosphonium salt reported by Hoge et al [36] also contain the mer-isomero ft he FAP anion.…”
Section: Nickel Complexesmentioning
confidence: 66%
“…Wasserscheid et al obtained as eries of silver salts by metathesis using AgNO 3 and KFAP in different solvents and investigated propene/propane separation using these salts. [38] The complexes [Co(h 5 -C 5 H 5 ) 2 ]FAP and [Ru(h 5 -C 5 H 5 )(h 6 -C 6 H 6 )]FAP have been prepared by anion exchange of the parentm etal chloridecomplexes with NaFAP. [39] Surprisingly,f luoridea bstraction from transition metal fluoride complexes by tris(pentafluoroethyl)difluorophosphorane is unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Silver salts are known to form π‐complexes with olefins, which makes them interesting in processes concerning the gas separation of mixtures of alkenes and alkanes . Recently, the silver salts [Ag(CH 3 CN) x ][P(C 2 F 5 ) 3 F 3 ] ( x= 2, 4) have been successfully applied in experiments for the separation of alkenes and alkanes . In order to investigate the gas separation capability of 1 g , we first conducted a blind test and stirred neat 1 g for 30 minutes in an atmosphere of a butane/propane mixture (85:15), without any detectable uptake of the gas.…”
Section: Resultsmentioning
confidence: 99%
“…[29] Recently,t he silver salts [Ag(CH 3 CN) x ][P(C 2 F 5 ) 3 F 3 ]( x = 2, 4) have been successfully applied in experiments fort he separation of alkenes and alkanes. [30] In order to investigate the gas separation capability of 1g,w ef irst conducted ab lind test and stirred neat 1g for 30 minutes in an atmosphere of ab utane/propane mixture (85:15), withouta ny detectable uptake of the gas. The treatment of 1g with isobutene during45minutes at room temperature, however, resulted in an absorption of isobutenea nd a liquefaction of the viscouss alt.…”
Section: Resultsmentioning
confidence: 99%
“…65 2) Å correspondingly. 71 Luminescence Properties. The design of transition-metal complexes or clusters with long-lived excited states and high emission quantum yields is a highly important task for modern coordination chemistry.…”
Section: ■ Introductionmentioning
confidence: 99%